Pengaruh Persepsi Harga, Lokasi dan Fasilitas terhadap Keputusan Pembelian Member di Armada Jhonson Gym Porong - Verizka, Meyda Ayu; Saqofa Nabilah Aini (Jurnal Ilmiah Ekonomika & Sains, 2025)
This study aims to analyze the influence of price perception, location, and facilities on membership purchasing decisions at Armada Jhonson Gym Porong, Sidoarjo. A quantitative approach using multiple linear regression was applied, involving 120 respondents from Millennial and Gen Z generations. The results indicate that facilities have a significant partial effect on purchasing decisions, while price perception and location are not significant. Simultaneously, all three variables significantly affect purchasing decisions with an F-test value of 2.825 and a significance level of 0.042, yet they only explain 6.8% of the variation in purchasing decisions (R² = 0,068). These findings confirm that facilities are the main factor encouraging consumers to join and maintain their membership. The study implies that gym management should focus on improving facilities and services to attract and retain members, especially Millennials and Gen Z, amid increasing competition in the fitness industry.